(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: Determine the rate of knowledge and practice about anemia prevention in women of reproductive age to come to the hospital in Binh Duong province in 2019. Methods: Descriptive cross-sectional study. The study was conducted by direct interviewing the research subjects according to the structure questionnaire. Results: Anemia knowledge score of research subjects is very low, average 26.2 ± 3.9 points (scale of 0-51). The practical score of anemia prevention subjects of the research subjects averaged 7.7 ± 1.8 points (scale of 0-11). The percentage of common knowledge about anemia prevention among women of childbearing age is very low, only 12.4%, but the rate of good general practice is relatively higher at 52.2%. The rate of good practice in the group of 40-49 years old was lower than that of the group of 18-29 years old (OR=0.32; 95%CI: 0.12-0.78; p<0.05); in the group of primary education level is lower than that of upper secondary school (OR = 0.18; 95% CI: 0.06-0.47; p < 0.05) and lower secondary school group (OR =0.42; 95%CI: 0.21-0.86; p<0.05). Conclusions: Knowledge and practice of anemia prevention and control among women of reproductive age who come to visit hospitals in Binh Duong province are still limited, need to focus on communication, health education and provision of supportive measures to improve anemia in women.